Transgressing boundaries: social reform, theology, and the demarcations between science and religion - Strube, Julian (Aries, 2016)
This editorial argues for a methodological move away from dichotomous constellations toward a concept of entangled history. Although the study of esotericism seeks to highlight the cultural importance of its subject, its leading approaches are reiterating the very polemical dichotomies that led to its marginalization. This can be seen as the grand paradox of the study of esotericism. Therefore it is necessary to transgress both disciplinary and geographical boundaries and understand “esotericism” as a deeply entangled element of complex global discourses about “religion,” “science,” and “politics.” This opens up new opportunities for the study of esotericism to not only better comprehend the emergence of “esotericism” as an integral part of “Western” culture, but also to contribute to an understanding of the emergence of “Western” identity in general.
Keywords: Geschichtsschreibung; Esoterik; Wissenschaft; Religion; Sozialreform